PENGEMBANGAN LKPD BERBASIS PROBLEM SOLVING PADA MATERI LITOSFER SISWA KELAS X SMA NEGERI 3 TEBING TINGGI - Selpi Indriani; Deni Puji Hartono (JURNAL SWARNABHUMI : Jurnal Geografi dan Pembelajaran Geografi, 2021)
The purpose of this study was to produce a problem solving based student worksheet product on the lithosphere material of class X SMA Negeri 3 Tebing Tinggi that was valid, practical, and effective. Schools try to provide learning tools that can support student learning activities, one of which is LKPD. LKPD has a function to measure the abilities possessed by students. LKPD is a ready-to-use worksheet, containing learning material and questions. The method used in this research is research and development. Based on the research results, the material expert validation sheet obtained an average value of 3.68 which is categorized as very good, and the total score is 70. On the media expert validation sheet, an average value of 2.83 is categorized as good, and the total score is 48. The resulting percentage is 480. On the linguist validation sheet, an average value of 3.6 is obtained which is categorized as very good, and the total score is 36. In the calculation results, the practicality level of the product reaches 99.97% and is categorized as very practical. Then on the results of the effectiveness of the product, the gain was 2.9, so it can be categorized as high. On the average result, the pre-test score is 69.66 and the post-test score is 89. There is a difference in the number of 19.34 and it is stated in the gain results. It can be said that there is a significant difference between the pre-test and post-test results.